Propuesta para la creación de un recetario adecuado para niños con diabetes - Castro Fernández, Cristian Alejandro (2021)
A compilation was made about the most relevant issues related to the problem of diabetes in children between 3 and 12 years old in order to establish the nutritional requirements of minors, as well as their problems. The root cause of the inconveniences that occur in children with diabetes was determined, according to relevant bibliographic information. In the research process, it was established to investigate professionals involved, a case study and a person living with this health problem through an interview, thanks to the applied instruments, it was possible to know that the psychological factor is very important in the field of diabetes and the most important thing is the first reaction of parents when knowing that their children were diagnosed with diabetes, influencing a lot in the child making him feel accepted or rejected. In the proposal, a recipe book was developed taking into account the recommendations of professionals, the preferences and tastes of patients who have this problem, establishing an appropriate diet, taking into account the ingredients and cooking methods.